A novel highly conductive, transparent, and strong pure-cellulose film from TEMPO-oxidized bacterial cellulose by increasing sonication power - Rahmadiawan, Dieter; Abral, Hairul; Kotodeli, Rafi Alzues; Sugiarti, Eni; Muslimin, Ahmad Novi; Admi, Ratna Isnanita; Arafat, Andril; Kim, Hyun-Joong; Sapuan, S. M.; Kosasih, Engkos Achmad (Multidisciplinary Digital Publishing Institute, 2023)
Developing a conductive cellulose film without any metal compounds remains challenging, though in great demand. However, cellulose film prepared from bacterial cellulose (BC) powder without any metal compounds has poor tensile, physical, and electrical properties, thus limiting its application. Herein, this study aims to prepare and characterize an all-cellulose film from 2,2,6,6-Tetramethylpiperidin-1-yl)oxyl (TEMPO)-oxidized bacterial cellulose (TOBC) powders without adding metal compounds and treated by ultrasonication. TOBC powders are sonicated with various powers of 250, 500, and 750 W for 20 min without any other substance. It was proved that increasing the ultrasonication power level resulted in a significant improvement in the properties of the film. The ultrasonication of 750 W increased tensile strength by 85, toughness by 308, light transmittance by 542, and electrical conductivity by 174 compared to the nonsonicated film. A light-emitting diode connected to a power source through this sonicated film was much brighter than that connected via a nonsonicated film. For the first time, this study reports the preparation of electrically conductive, transparent, strong, and bendable pure TOBC films by increasing ultrasonic power for environmentally friendly electronic devices application.